2004
DOI: 10.1097/01.ju.0000138341.68365.b6
|View full text |Cite
|
Sign up to set email alerts
|

Midline Dorsal Plication Technique for Penile Curvature Repair

Abstract: Midline dorsal penile plication is a safe, simple to perform procedure that achieves excellent results in patients with mild to moderate curvature. It is a useful technique in patients in who previous repairs have failed. We suggest other repair techniques for severe curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…According to his anatomical studies, dissection in the dorsal aspect beyond 1–11 O’clock has a higher risk of injuring the nerve pedicle. The dorsal plication is performed with one or two parallel stitches, and, good results have also been reported by other surgeons ( 32 , 33 ).…”
Section: Dorsal Plication Techniquementioning
confidence: 75%
See 2 more Smart Citations
“…According to his anatomical studies, dissection in the dorsal aspect beyond 1–11 O’clock has a higher risk of injuring the nerve pedicle. The dorsal plication is performed with one or two parallel stitches, and, good results have also been reported by other surgeons ( 32 , 33 ).…”
Section: Dorsal Plication Techniquementioning
confidence: 75%
“…Some potential disadvantages with the Baskin technique include the presence of dorsal suture (which may be bothersome for some patients) and limited effectiveness when used in older patients as these sutures may not support the pressure exerted by erections in these patients during intercourse ( 34 ). In patients with low-grade curvature, recurrence of penile curvature after plication on the dorsal surface was reported in 7% of patients ( 32 ).…”
Section: Dorsal Plication Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…There are many techniques described for the repair of penile curvature with or without hypospadias. [13][14][15][16][17][18][19] The incidence of penile curvature associated with hypospadias is not clear. Baskin et al 20,21 found significant penile curvature in 25% of patients after releasing the skin and dartos in patients with hypospadias who underwent island flap reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…When the penile curvature repair is performed, the midline dorsal penile plication technique involves the mobilization of the right and left neurovascular bundle. Near the pubic bone, nervus dorsalis penis can be easily contused or traversed [55].…”
Section: Clinical Considerations Of Nervus Dorsalis Penis/clitoridismentioning
confidence: 99%